2020
DOI: 10.1016/j.cmi.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A simplified blood culture sampling protocol for reducing contamination and costs: a randomized controlled trial

Abstract: Objectives: Blood culture contamination carries risks for patients, such as unnecessary antimicrobial therapy and other additional hazards and costs. One method shown to be effective in reducing contamination is initial blood specimen diversion during collection. We hypothesized that initial blood specimen diversion without a designated device or procedure would suffice for reduction in blood culture contamination rate. Methods: From 1 September 2017 through to 6 September 2018, we conducted a randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…However, as some bacteria and fungi are difficult to grow in culture, the sensitivity of these inspection techniques is unsatisfactory ( 3 ) and not fit for purpose for acute serious infections, such as sepsis in patients with a blood disease, especially those undergoing HSCT. Moreover, the times required for Gram staining, organism identification (ID), and antimicrobial susceptibility testing for blood cultures are 1 day, 2 days, and 3 days, respectively ( 4 , 5 ). The average turnaround time for anal swab samples, a common method for early detection of carbapenem-resistant Enterobacter (CRE) spp., is 2 to 4 days ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as some bacteria and fungi are difficult to grow in culture, the sensitivity of these inspection techniques is unsatisfactory ( 3 ) and not fit for purpose for acute serious infections, such as sepsis in patients with a blood disease, especially those undergoing HSCT. Moreover, the times required for Gram staining, organism identification (ID), and antimicrobial susceptibility testing for blood cultures are 1 day, 2 days, and 3 days, respectively ( 4 , 5 ). The average turnaround time for anal swab samples, a common method for early detection of carbapenem-resistant Enterobacter (CRE) spp., is 2 to 4 days ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results were much higher than the recommended target rate of 3% for BCC in adults [ 10 ]. Lalezari et al report that 50% of all positive blood cultures were found to contain contaminants [ 27 ]. Washer et al found 13% of all positive blood cultures appeared to be contaminated, and that overall blood contamination rates were 0.8% among cultures obtained peripherally by phlebotomists [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chart then starts with the second CSN, and the NBP between the first and the second CSN. [7][8] We used median of total NBP to define the center line (CL), and used confidence intervals to define control limits of the chart. The confidence intervals were calculated using equations proposed by Yang Z et al 9 The equation for lower limit is ln(1 -α/2)/ln(q) and the equation for upper limit is ln(α/2)/ln(q)-1 ,where α is the cumulative probability and q is the probability of a non-contaminated specimens.…”
Section: Discussionmentioning
confidence: 99%